In Vivo and In Silico Study of the Antinociceptive and Toxicological Effect of the Extracts of Petiveria alliacea L. Leaves - Kelly del Carmen Cruz-Salomón; Rosa Isela Cruz-Rodríguez; Josué Vidal Espinosa-Juárez; Abumalé Cruz-Salomón; Alfredo Briones-Aranda; Nancy Ruiz-Lau; Víctor Manuel Ruíz-Valdiviezo (MDPI AG, 2022)
Petiveria alliacea L. is an herb used in traditional medicine in Mexico and its roots have been studied to treat pain. However, until now, the antinociceptive properties of the leaves have not been investigated, being the main section used empirically for the treatment of diseases. For this reason, this study aimed to evaluate the antinociceptive and toxoicological activity of various extracts (aqueous, hexanic, and methanolic) from P. alliacea L. leaves in NIH mice and to perform an in silico analysis of the phytochemical compounds. Firstly, the antinociceptive effect was analyzed using the formalin model and the different doses of each of the extracts that were administered orally to obtain the dose-response curves. In addition, acute toxicity was determined by the up and down method and serum biochemical analysis. Later, the phytochemical study of extracts was carried out by thin layer chromatography (TLC) and visible light spectroscopy, and the volatile chemical components were analyzed by gas chromatography-mass spectrometry (GC/MS). Moreover, the most abundant compounds identified in the phytochemical study were analyzed in silico to predict their biological activity (PASSonline) and toxicology (OSIRIS Property Explorer). As a result, it was known that all extracts at doses from 10 to 316 mg/kg significantly reduced the pain response in both phases of the formalin model, with values of 50-60% for the inflammatory response. The toxicological studies (DL50) exhibited that all extracts did not cause any mortality up to the 2000 mg/kg dose level. This was corroborated by the values in the normal range of the biochemical parameters in the serum. Finally, the phytochemical screening of the presence of phenolic structures (coumarins, flavonoids) and terpenes (saponins and terpenes) was verified, and the highest content was of a lipid nature, 1.65 ± 0.54 meq diosgenin/mL in the methanolic extract. A total of 54 components were identified, 11 were the most abundant, and only four (Eicosane, Methyl oleate, 4-bis(1-phenylethyl) phenol, and Ethyl linolenate) of them showed a probability towards active antinociceptive activity in silico greater than 0.5. These results showed that the P. alliacea L. leaf extract possesses molecules with antinociceptive activity.